1984
DOI: 10.7164/antibiotics.37.1231
|View full text |Cite
|
Sign up to set email alerts
|

Activity of rapamycin (AY-22,989) against transplanted tumors.

Abstract: Rapamycin is a triene antibiotic produced by Streptonrvces hygroscopicus1,2). Structure elucidation revealed the presence of a pipecolic acid residue in the macrolide3.4). Several yeasts, as well as yeast-like and filamentous fungi, are sensitive to rapamycin; however, the main feature of the antibiotic is its high activity against Candida albicans (MIC 0.02 ~ 0.20 tcg/ml)5). Nucleic acids synthesis inhibition and degradation in C. albicans are the primary modes of action6). The LD50 ip of rapamycin in the mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(158 citation statements)
references
References 9 publications
1
149
0
3
Order By: Relevance
“…Our "Tumor Protocol" was planned to minimize the potential impact of steroids 12 and calcineurin-inhibitors 6 on HCC recurrence, and to allow for benefits of the previously reported antitumor activity of sirolimus. [13][14][15] In the absence of a control group, we cannot conclude that our protocol prevented tumor recurrence or prolonged survival in cases with tumor recurrence.…”
Section: Discussionmentioning
confidence: 90%
“…Our "Tumor Protocol" was planned to minimize the potential impact of steroids 12 and calcineurin-inhibitors 6 on HCC recurrence, and to allow for benefits of the previously reported antitumor activity of sirolimus. [13][14][15] In the absence of a control group, we cannot conclude that our protocol prevented tumor recurrence or prolonged survival in cases with tumor recurrence.…”
Section: Discussionmentioning
confidence: 90%
“…However, different immunosuppressant medications may have varying effects on cancer risk following transplantation. In particular, mammalian target of rapamycin (mTOR) inhibitors, a class of immunosuppressants, have anti-carcinogenic properties (3,4). The mTOR is a protein that plays a key role in an important signaling pathway that controls cellular growth and proliferation (5).…”
Section: Introductionmentioning
confidence: 99%
“…7 MTIs also have been shown to be active against a wide variety of tumor types. [8][9][10] We have previously shown that rapamycin induces apoptosis in precursor B ALL lines in vitro and has in vivo activity in transgenic mice with pre-B leukemia/lymphoma. 11 Second generation MTIs, CCI-779 and RAD-001, are currently in phase 1 to phase 3 clinical trials in patients with various cancers, [12][13][14][15] but preclinical studies have not previously been performed in primary human ALL.…”
Section: Introductionmentioning
confidence: 99%